Electrochemical detection of ofloxacin with MoS2/RGO composite sensor - Mohit; Bhardwaj Vineet; Thakur Kamal Kishor (E3S Web of Conferences, 2024)
This work presents the development and utilization of a MoS2/RGO nanocomposite sensor for the quantification of ofloxacin. The fabrication of this sensor is based on the combination of graphite oxide and MoS2 as fundamental components. The special shape ordered atomic arrangement, and flatness of the MoS2/RGO nanocomposite have made the sensor more sensitive and able to detect smaller amounts of the target substance. Cyclic voltammetry was employed in the sensing investigation, where the relationship between current and potential was explored using a modified glassy carbon electrode. The data explicitly demonstrates that MoS2/RGO exhibits a substantially higher peak current (22.0–33.9 µA) and considerably lower overpotential (0.27–0.12 V) compared to MoS2 alone. This translates to a significant enhancement in sensitivity (89.89 A/cm²) and detection limit (18.89 µM) for MoS2/RGO. These remarkable improvements are attributed to the nanocomposite's facilitated charge transfer, increased specific surface area, and superior conductivity.